Resultado do acompanhamento clínico-radiológico pós-cirúrgico do condroblastoma Results from clinical and radiological follow-up, after surgical treatment of chondroblastoma - Valter Penna; Eduardo Areas Toller; Adriano Jander Ferreira; Dante Palloni Costa Dias (Revista Brasileira de Ortopedia, 2011)
OBJETIVO: Avaliar o resultado clínico e radiológico, a longo prazo, de pacientes submetidos ao tratamento cirúrgico do condroblastoma, entre 2003 e 2009, pela mesma equipe cirúrgica e empregando a mesma técnica operatória. MÉTODOS: Foi realizado estudo retrospectivo de 12 pacientes com diagnóstico histológico de condroblastoma, atendidos entre 2003 e 2009, na Fundação Pio XII (Hospital de Câncer de Barretos - Barretos, SP) e submetidos ao tratamento cirúrgico com ressecção intralesional, adjuvância com eletrocauterização e substituição por metilmetacrilato (11 casos) ou enxerto ósseo autólogo de crista ilíaca (um caso). A avaliação pré-operatória incluía exame físico, radiografias simples do local, ressonância nuclear magnética ou tomografia axial computadorizada local, além de cintilografia óssea. Os pacientes foram avaliados clínica e radiologicamente, segundo protocolo predefinido, com radiografias seriadas e avaliação funcional, conforme o escore funcional de Enneking. RESULTADOS: A idade média do diagnóstico foi de 14A e 4M, sendo o local preferencial de acometimento a epífise distal do fêmur (75%), seguido pela tíbia proximal (16,6%) e calcâneo (8,4%). Houve prevalência maior no sexo masculino em relação ao sexo feminino (3:1). Em três casos houve necessidade prévia de biópsia. Durante o seguimento, não evidenciamos recidiva local do tumor e todos os pacientes apresentaram excelente resultado funcional, com escore de Enneking entre 20 e 30, com a técnica cirúrgica empregada. CONCLUSÃO: O tratamento cirúrgico do condroblastoma, com ressecção intralesional, uso de adjuvância, com eletrocauterização e substituição por metilmetacrilato ou enxerto ósseo produz bons resultados. OBJECTIVES: To evaluate the long-term clinical and radiological results from patients who underwent surgical treatment of chondroblastoma, between 2003 and 2009, by the same surgical team, using the same operative technique. METHODS: A retrospective study was conducted on 12 patients with histological diagnoses of chondroblastoma, who were attended between 2003 and 2009 at the Pius XII Foundation (Barretos Cancer Hospital, Barretos, State of São Paulo). These patients underwent surgical treatment with intralesional resection of the tumor, adjuvant electrocauterization and replacement with methyl methacrylate (11 cases) or an autologous graft from the iliac crest (one case). The preoperative evaluation included physical examination, plain radiographs of the site, magnetic resonance imaging, computed axial tomography and bone scintigraphy. The patients were assessed clinically and radiologically according to a predefined protocol, with a series of plain radiographs, and a functional assessment in accordance with the Enneking functional score. RESULTS: The average age at the time of diagnosis was 14 years and 4 months. The most frequent location affected was the distal femoral epiphysis (75%), followed by the proximal tibial epiphysis (16.6%) and the calcaneus (8.4%). There was higher prevalence among the female patients than among the male patients (3:1). In three cases, preoperative biopsy was necessary. During the follow-up, there was no evidence of local tumor recurrence, and all the patients presented an excellent functional result from the surgical technique used, with Enneking scores ranging from 20 to 30. CONCLUSION: Surgical treatment of chondroblastoma, using intralesional resection, adjuvant electrocauterization and replacement with methyl methacrylate or bone graft produced good results.